Reproductive success of the ambrosia beetle Platypus quercivorus on Quercus laurifolia planted in Japan - YAMASAKI, Michimasa; IIZUKA, Hiroaki; FUTAI, Kazuyoshi (Forest research, Kyoto, 2012)
Mortality of Quercus laurifolia trees that had been planted in Japan occurred in 2006. This was caused by an attack by the ambrosia beetle Platypus quercivorus, which causes a disease called Japanese oak wilt and results in mass mortality of Fagaceae trees in Japan. In order to study the infestation of Q. laurifolia by P. quercivorus, dead trees were cut into bolts, and the density of holes bored by P. quercivorus was examined for each bolt. Tube traps were attached to each hole in the bolts of the cut trees, and the number of offspring that emerged from the hole during 2007 (the year following the infestation) was counted. Similar to other Japanese Fagaceae species, the density of holes bored by P. quercivorus decreased with increase in the height of Q. laurifolia. The sex ratio of the emerged beetle was biased towards males, and the number of offspring per hole ranged from 0 to 41. The effects of the height and the hole density on the number of offspring were analyzed with zero-altered negative binomial models with a hurdle component and a truncated count component. The results of the hurdle component in the model for zero counts showed that the probability that one or more beetles emerged from holes was negatively affected by the height above the ground. According to the results of the count component of the model for positive counts, the number of offspring showed a unimodal distribution, with a peak at around one in the density of holes per 100 cm2.